Discriminating between Cell Surface and Intracellular Plasminogen-binding Proteins: Heterogeneity in Profibrinolytic Plasminogen-binding Proteins on Monocytoid Cells - Hawley, Stephen B.; Green, Michael A.; Miles, Lindsey A. (Thrombosis and Haemostasis, 2000)
When plasminogen binds to cell surfaces, its activation is markedly enhanced compared to soluble plasminogen. Although several distinct molecules may contribute to plasminogen binding to a given cell type, the subset of plasminogen receptors responsible for enhancing plasminogen activation expose a carboxyl-terminal lysine on the cell surface and are sensitive to proteolysis by carboxypeptidase B (CpB). To distinguish this subset of plasminogen receptors from plasminogen-binding proteins that are not profibrinolytic, we treated intact U937 monocytoid cells and peripheral blood monocytes with CpB to remove exposed carboxyl-terminal lysines, and subjected the membrane proteins to two-dimensional gel electrophoresis followed by ligand blotting with 125I-plasminogen. Western blotting was performed with antibodies against previously characterized candidate plasminogen receptors to identify plasminogen-binding proteins on the two-dimensional ligand blots. Densitometry of autoradiograms of the 125I-plasminogen ligand blots of U937 cell membranes revealed that membraneassociated α-enolase, actin and annexin II showed minimal changes in 125I-plasminogen binding following CpB treatment of intact cells, suggesting that these proteins are not accessible to CpB on the U937 cell surface and most likely do not serve as profibrinolytic plasminogen receptors on U937 cells. In contrast, densitometry of autoradiograms of 125I-plasminogen ligand blots of monocyte membranes revealed that 125I-plasminogen binding to α-enolase was reduced 71% by treatment of intact cells with CpB, while binding to annexin II was reduced 14%. Thus, a portion of membrane-associated α-enolase and annexin II expose carboxyl terminal lysines that are accessible to CpB on the peripheral blood monocyte surface, suggesting that these molecules may serve as profibrinolytic plasminogen receptors on monocytes. Our data suggest that U937 cells and peripheral blood monocytes have distinct sets of molecules that constitute the population of cell surface profibrinolytic plasminogen-binding proteins. Furthermore, our data suggest that while several plasminogen-binding proteins with carboxyl terminal lysines are associated with cell membranes, only a small subset of these proteins expose a carboxyl terminal lysine that is accessible to CpB on the cell surface.The abbreviations used are: 2D, two-dimensional; 2D-PAGE, two-dimensional polyacrylamide gel electrophoresis; BSA, bovine serum albumin; CpB, carboxypeptidase B; EACA, є-aminocaproic acid; HBSS, Hanks’ Balanced Salt Solution supplemented with 20 mM HEPES; HBSS-BSA, HBSS with 0.1% bovine serum albumin; HRP, horseradish peroxidase; IEF, isoelectric focusing; PBS, phosphate buffered saline; PMSF, phenylmethylsulfonyl fluoride; PVDF, polyvinylidene difluoride; SDS, sodium dodecyl sulfate; SDSPAGE, sodium dodecyl sulfate polyacrylamide gel electrophoresis; TBST, Tris buffered saline with 0.1% Tween 20; uPAR, urokinase-type plasminogen activator receptor.
Keywords: Plasminogen; receptor; fibrinolysis; U937; monocyte